Data Reduction with the MIKE Spectrometer. (4th January 2016) - Bernstein, Rebecca M.; Burles, Scott M.; Prochaska, J. Xavier
Abstract: This manuscript describes the design, usage, and data-reduction pipeline developed for the Magellan Inamori Kyocera Echelle (MIKE) spectrometer used with the Magellan telescope at the Las Campanas Observatory. We summarize the basic characteristics of the instrument and discuss observational procedures recommended for calibrating the standard data products. We detail the design and implementation of an IDL-based data-reduction pipeline for MIKE data (since generalized to other echelle spectrometers, e.g., Keck/HIRES, VLT/UVES). This includes novel techniques for flat-fielding, wavelength calibration, and the extraction of echelle spectroscopy. Sufficient detail is provided in this manuscript to enable inexperienced observers to understand the strengths and weaknesses of the instrument and software package and an assessment of the related systematics.